Hubungan Pupuk Kalium dan Kebutuhan Air terhadap Sifat Fisiologis, Sistem Perakaran dan Biomassa Tanaman Jagung (Zea mays) - Dwi Astutik; Damar Suryaningndari; Usfri Raranda (JURNAL CITRA WIDYA EDUKASI, 2019)
Water and nutrient requirements affected Corn growth and development. The essensial role of potassium was found in various plant metabolism aspects such as plant physiology,assimilate transportation and translocation and plant resistances of drought. Sufficient water needed to support plnt growth because excee lack of water can disrupt and inhibit the metabolims process. The research aimed to determine physiological, root systems and biomass of corn plants effected potassium and water deficiency. The research had been conducted at the Faculty of Agriculture Greenhouse at Gadjah Mada University Yogyakarta in April-June 2016. The experiment design used factorial Completely Randomized Design with 2 factors and three replications. The first factor was the dose of KCl (K) fertilizer consisting of KCl 0 kg/ha (K1) and KCl 100 kg/ha (K2). The second factor was enough water (watering every day/ A1) and Less water (watering 4 days/ A2). The data observed were analyzed by ANOVA (analysis of variance) and least significant defference (LSD) test at alpha 5%. Potassium had an effect on the parameters of chlorophyll a, chlorophyll b, total chlorophyll, and root area surface of corn at 4 MST. Potassium affected to stem dry weight, primary roots, and root volume at 8 MST. Watering treatment had an effect on chlorophyll a, chlorophyll b, and total chlorophyll at 4 MST. There were interactions between potassium and water treatments on root volume parameters at 8 MST.